To bring out the best of us: a look at the school from humanistic psychology - Arboccó de los Heros, Manuel (2020)
The following essay proposes to seek reflection on some difficulties that have been happening in the school and social sphere, such as mistreatment of students and teachers,  technological harassment between schoolchildren, the absence of parental work or neglect emotional of gifted students, and this from data that speaks of a significant group of children with a school phobia. In addition, it emphasizes the role of education and teachers as agents of change to improve the situation and try to regain joy and hope in addition to going to learn at school, assist to properly link us and be happy. The work is divided into 5 points as sections: a. introduction; b. present problems; c. what we should promote; d. to bring out the best in us; e. conclusion: regaining hope.